2021
DOI: 10.1088/1361-6560/ac176a
|View full text |Cite
|
Sign up to set email alerts
|

An unsupervised learning approach to ultrasound strain elastography with spatio-temporal consistency

Abstract: Quasi-static ultrasound elastography (USE) is an imaging modality that measures deformation (i.e. strain) of tissue in response to an applied mechanical force. In USE, the strain modulus is traditionally obtained by deriving the displacement field estimated between a pair of radio-frequency data. In this work we propose a recurrent network architecture with convolutional long-short-term memory decoder blocks to improve displacement estimation and spatio-temporal continuity between time series ultrasound frames… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…However, the difference in terms of displacement accuracy between ReUSENet and USENet is not as important as in our previous work on quasi-static elastography, where we showed that feed-forward networks failed to estimate large range quasi-static deformations. 7 In shear wave imaging, the displacement generated is in the order of a few micrometres, and the ultrasound time series are acquired with a high temporal sampling rate (about 5-10 ms). Therefore, our results suggest that both feed-forward and recurrent neural networks can efficiently track shear wave displacements, and that the use of convLSTM units is better suited for ultrasound time series that exhibit larger deformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the difference in terms of displacement accuracy between ReUSENet and USENet is not as important as in our previous work on quasi-static elastography, where we showed that feed-forward networks failed to estimate large range quasi-static deformations. 7 In shear wave imaging, the displacement generated is in the order of a few micrometres, and the ultrasound time series are acquired with a high temporal sampling rate (about 5-10 ms). Therefore, our results suggest that both feed-forward and recurrent neural networks can efficiently track shear wave displacements, and that the use of convLSTM units is better suited for ultrasound time series that exhibit larger deformations.…”
Section: Discussionmentioning
confidence: 99%
“…The architecture of both neural networks used in this study has been described in details in our previous works, and are named USENet and ReUSENet for '(Recurrent) Ultrasound Elastography Network'. 7 They both consist in an encoder-decoder neural network with skip connections. The encoder part is the same for both networks, and is composed of four down-sampling ResNet blocks.…”
Section: Unsupervised Training Strategy and Network Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, deep learning methods have gained popularity in strain elastography ( [17], [18], [19], [20]) and SWE-imaging ( [21], [22], [23]). These methods allow estimates without intensive preprocessing of the data, manual tuning and do not rely on feature extraction, e.g., the shear wave velocity for elasticity estimation.…”
Section: Introductionmentioning
confidence: 99%
“…They have been successfully adopted for USE by modifying the architectures to handle high-frequency radio-frequency (RF) data [14,6]. Unsupervised and semi-supervised techniques have also been employed to train the networks using real US data without requiring the ground truth displacements [13,1,2,15]. They employed prior knowledge of displacement continuity in the form of the first-and second-derivative regularizers.…”
Section: Introductionmentioning
confidence: 99%